2001
DOI: 10.1348/000711201160830
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of self‐regulation in adolescent patients with anorexia nervosa

Abstract: The purpose of the study was to investigate the different modes of self-regulation in adolescent anorexia nervosa (AN). A self-system questionnaire, the Narcissism Inventory, was given to 61 adolescent females with AN and 61 controls. Patients with AN reported higher overall disturbances in self-regulation than controls. In particular, a highly unstable self-system, a tendency to use idealization as modus of regulation, and high narcissistic gain from their illness was found in the patient group; however, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 17 publications
1
14
0
Order By: Relevance
“…This corroborates individual studies which report that people with EDs are more aware than HCs of social presentation and comparison (public self-consciousness) and reflect more in private on how they compare with others (private self-consciousness; Cardi et al, 2014;Forbush & Watson, 2006;Ille et al, 2014). People with AN judge themselves by high external standards which they feel that they do not successfully attain (Gunnard et al, 2012;Karwautz et al, 2001aKarwautz et al, ,2001b. This predicts body dissatisfaction and drive for thinness (Buchholz et al, 2007).…”
Section: (2) Modifying Situations Situation Modification Involves Exsupporting
confidence: 80%
See 2 more Smart Citations
“…This corroborates individual studies which report that people with EDs are more aware than HCs of social presentation and comparison (public self-consciousness) and reflect more in private on how they compare with others (private self-consciousness; Cardi et al, 2014;Forbush & Watson, 2006;Ille et al, 2014). People with AN judge themselves by high external standards which they feel that they do not successfully attain (Gunnard et al, 2012;Karwautz et al, 2001aKarwautz et al, ,2001b. This predicts body dissatisfaction and drive for thinness (Buchholz et al, 2007).…”
Section: (2) Modifying Situations Situation Modification Involves Exsupporting
confidence: 80%
“…Nine studies measured avoidance of emotion-provoking situations. All studies found greater reported avoidance by people with EDs relative to HCs, with meta-analysis of six studies supporting this conclusion within samples of people with AN [d = 1.00 (95% CI: 0.56, 1.45), p b 0.000] (Holliday, Tchanturia, Landau, Collier, & Treasure, 2005;Karwautz et al, 2001aKarwautz et al, , 2001b; see Appendix A for metaanalyses references). Experiential avoidance is associated with ED and AN symptomatology (Corstorphine, Mountford, Tomlinson, Waller, & Meyer, 2007;Lampard, Byrne, McLean, & Fursland, 2011;Rawal, Park & Williams, 2010;Raykos, Byrne, & Watson, 2009).…”
Section: Antecedent-focussed Er In Anmentioning
confidence: 74%
See 1 more Smart Citation
“…Comparison with previous work on temperament, character, and personality traits It was Strober (1991) who first integrated the organismic approach to temperament by Cloninger into a model of aetiology for AN focusing on self-development (Karwautz et al, 2001b). In terms of these dimensions of personality (temperament and character) the women with AN differed markedly from their sisters, scoring lower in novelty seeking, self-directedness, and cooperativeness, and higher in harm avoidance, persistence, and self-transcendence and higher in all the dimensions of the EDI-2.…”
Section: Comparison With Previous Work On Axis-ii Comorbiditymentioning
confidence: 99%
“…Early studies reported that higher narcissism was associated with more positive body image (Jackson, Ervin, & Hodge, 1992) and lower incidence of disordered eating in women (e.g., Karwautz et al, 2001;Steinberg & Shaw, 1997), although relationships among men have been more equivocal (Brown & Graham, 2008;Davis, Karvinen, & McCreary, 2005). A limitation of these studies, however, is in their treatment of narcissism as a homogeneous concept.…”
Section: Introductionmentioning
confidence: 99%